2007
DOI: 10.1111/j.1447-0756.2007.00502.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolated torsion of fallopian tube in a premenarcheal 12‐year‐old girl

Abstract: Isolated torsion of fallopian tubes should be considered even at premenarcheal ages in cases of acute pelvic pain, and prompt surgery can preserve the tube and thus fertility. It is an uncommon emergency event and a difficult condition to evaluate clinically. This report focuses on a 12-year-old premenarcheal girl who presented with acute pelvic pain of 2 days. Pelvic ultrasound showed an adnexal mass on the left side. Laparoscopy was performed and an isolated tubal torsion was discovered. The tube was necroti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 4 publications
0
29
0
5
Order By: Relevance
“…Only one case report describes a prepubertal girl below the age of 10 years [11]. Nine other prior cases are described in medical literature, reporting about premenarchal girls at or above the age of 10 years [1,4,5,7,[9][10][11]19]. …”
Section: Overview Of Literaturementioning
confidence: 96%
“…Only one case report describes a prepubertal girl below the age of 10 years [11]. Nine other prior cases are described in medical literature, reporting about premenarchal girls at or above the age of 10 years [1,4,5,7,[9][10][11]19]. …”
Section: Overview Of Literaturementioning
confidence: 96%
“…According to the cases that have been reported to date, three possible etiologies might be responsible: [1] adnexal torsion, [2] tubal and ovarian maldevelopment secondary to ischemia due to a vascular accident, and [3] a defect in the development of the M€ ullerian and mesonephric system, either entirely on one side or localized to the region of the genital ridge and the caudal part (1,(4)(5)(6).…”
Section: Discussionmentioning
confidence: 99%
“…Adnexal torsion can be related to either the tube or the ovary or to both. Although it is thought to be rare before menarche and after menapause, Jamieson and Soboleski [21] and Goktolga et al [22] reported adnexal torsion in prepuberty. Torsion most likely manifests itself with acute abdominal pain, nausea, and vomiting, but it can also be asymptomatic and therefore diagnosed only in operations performed for other reasons.…”
Section: Discussionmentioning
confidence: 99%